Reading Nietzsche : an analysis of Beyond good and evil - Burnham, Douglas (Acumen, 2007)
Beyond Good and Evil is one of the classics of western philosophy. Pithy, lyrical and densely complex, it demands that its readers are already familiar with key Nietzschean concepts - such as the will-to-power, perspectivism or eternal recurrence - and are able to leap with Nietzschean agility from topic to topic, across metaphysics, psychology, religion, morality and politics. As a concise and comprehensive statement of Nietzsche's mature philosophy, it has served many readers as the point of entry into Nietzsche's work as a whole. Reading Nietzsche is an authoritative, insightful and detailed examination of this landmark text. It explains the central concepts, the range of Nietzsche's concerns, and highlights Nietzsche's writing strategies that are key to understanding his work and his processes of thought. In its close analysis of the text, Reading Nietzsche reassesses this most creative of philosophers and presents a significant contribution to the study of his thought. In setting this analysis within a comprehensive exposition of Nietzsche's ideas, the book serves as a guide both to Beyond Good and Evil and to Nietzsche's philosophy more generally.